Tinjauan Penerepan Prinsip Tanggung Jawab Negara dalam Kasus Spartly Island antara Filipina dan China - Ikhwan Ahmad Fiqqih; Irawati (Bandung Conference Series: Law Studies, 2024)
China's territorial claim over the Spratly Islands, particularly concerning its rich natural resources and escalating military activities, has created tension in the region, notably affecting the sensitivity of the Philippines. The legal actions taken by the Philippines in the International Tribunal, based on UNCLOS, resulted in a verdict affirming the lack of legal basis for China's claims and denying China any entitlement to an Exclusive Economic Zone within the Spratly Islands. Moreover, it was found that China had damaged the ecosystem in the Spratly Islands through activities such as overfishing and the construction of artificial islands. Despite the binding nature of the ruling, China has refused to accept or respect it. This research explores the implications arising from China's rejection of the ruling on the integrity of international maritime law, which has become an integral part (jus cogens). UNCLOS, as a crucial milestone in territorial sovereignty delineation, reinforces legal principles above a nation's economic or political strength. China, as a signatory to UNCLOS, has ratified this convention, yet its post-verdict stance raises questions about its consistency in adhering to widely recognized principles.The principle of responsibility for the violation of agreements can be applied in the context of China's rejection of the court's decision, where China is one of the participating countries and has ratified UNCLOS. As a participating state in the Convention, China is formally obligated to comply with the provisions of the convention based on the principle of Pacta Sunt Servanda and good faith. The Arbitration Court, as stipulated in UNCLOS, has jurisdiction, embodied as a compromissory clause or a specific arbitration clause, in case of disputes regarding the interpretation and application of the convention among the parties. This jurisdiction empowers the court to settle disputes that arise. As a dispute resolution institution, the arbitration court has the authority to decide on the disputes brought before it. The decisions issued by the arbitration are final and binding on all parties involved. Abstrak. Klaim territorial China terhadap Pulau Spratly, terutama dalam konteks sumber daya alam yang kaya, serta aktivitas militer yang terus meningkat, telah menciptakan ketegangan di kawasan, khususnya menyentuh sensitivitas Filipina. Tindakan hukum Filipina di Mahkamah Arbitrase Internasional, berdasarkan UNCLOS, menghasilkan putusan yang menegaskan kurangnya landasan hukum dari klaim China dan tidak ada apapun di Kepulauan Spartly yang memberikan Cina hak Zona Ekonomi Ekslusif serta telah merusak ekosistem di Kepulauan Spartly dengan aktivitas seperti penangkapan ikan berlebihan dan menciptakan pulau buatan. Meski putusan tersebut mengikat, China menolak untuk menerima dan menghormatinya.Penelitian ini menggali implikasi yang muncul dari penolakan China terhadap putusan tersebut terhadap kehormatan hukum laut internasional yang telah menjadi bagian integral (jus cogens). UNCLOS, sebagai tonggak penting dalam pembagian kedaulatan teritorial, menegaskan prinsip hukum di atas kekuatan ekonomi atau politik suatu negara. China, sebagai negara peserta UNCLOS, telah meratifikasi konvensi ini, namun sikapnya pasca-putusan menimbulkan pertanyaan tentang konsistensi pelaksanaannya terhadap prinsip-prinsip yang diakui secara luas.Prinsip tanggung jawab atas pelanggaran perjanjian dapat diterapkan dalam konteks kasus Penolakan China terhadap putusan mahkamah, yang mana China merupakan salah satu negara peserta dan telah meratifikasi UNCLOS, maka sebagai negara peserta Konvensi China berkewajiban secara formal untuk mematuhi isi ketentuan konvensi didasarkan dengan Asas Pacta Sunt Servanda dan itikad baik (good faith). Mahkamah Arbitrase sebagaimana ketentuan UNCLOS memiliki yuridiksi, yang tertuang sebagai clause compromissiore atau klausula tambahan arbitrase yang bersifat khusus, apabila timbul sengketa mengenai interpretasi penerapan konvensi antara para pihak. Yuridiksi tersebut memberikan mahkamah kewenangan untuk menyelesaikan sengketa yang terjadi. Sebagai lembaga penyelesaian sengketa mahkamah arbitrase memiliki kedudukan untuk memutuskan sengketa yang diajukan kepadanya. Keputusan yang dikeluarkan arbitrase tersebut bersifat final dan mengikat bagi semua pihak yang terlibat